(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The concept of Cherish Dating Restaurant is having a dating registration form for single and ready-to-mingle people and a random date registration for the willing person to register. A side of the uniqueness of the restaurant serves local cuisine with a twist that the customers have not tried before, such as buffalo chicken feet with peanut butter and creamy chop suey tahong chowder with creamy chowder. Cherish Dating Restaurant has five kinds of bundle food and a 5%discount for each bundle. Cherish Dating Restaurant has a great ambiance that would make people feel that they came to the past and make people at home. The research method used was descriptive research. The proponents surveyed 50 respondents composed of students, unemployed individuals, employed individuals, and residents of Vista Verde, North Kaybiga, Caloocan City. This study also used the financial statement to know if the business will become productive and is feasible. The researchers were also concerned about the return on investment (ROI). The results of this study showed the viability of the business, thereby proving a great market deal. The customers are willing to register the dating registration in our restaurant. In terms of the financial aspect, Cherish Dating Restaurant is indeed acceptable and profitable to the market although most Filipinos love eating outside. The business is well-maintained and managed based on the ROI of 0.94% circulation every year. The restaurant business is one of the most competitive businesses in the Philippines. It is feasible to the market due to the quality of the product. The researchers recommended developing products, enhancing its food service, and promoting or innovating new ideas to achieve customer satisfaction and loyalty of the customer. The researchers also recommended that future researchers should have an effective plan for the ROI in the same year for financial viability.